Plants in the clouds: vascular epiphytes of Pedra Azul, a mountain top in Espírito Santo, Southeastern Brazil - Marcusso, Gabriel Mendes [UNESP]; Neto, Luiz Menini; Lombardi, Julio Antonio [UNESP] (FapUNIFESP (SciELO), 2022)
Cloud forests usually occur at high-altitude sites of the Atlantic Forest in eastern Brazil, albeit scattered and fragmented along the mountain tops. In this habitat, the vegetation occurs at low-temperature conditions and is usually provided by additional water sources that arise due to the horizontal precipitation of the frequent fogs. Together with the more considerable air movement and higher luminosity, these factors are conditioning for singular floras at high elevations, mainly the vascular epiphytes, which are macro and microclimate dependent. In the mountains range at the center of the Espírito Santo state, Southeastern Brazil, some mountain tops such as Pedra Azul (PA) hold these environmental features. Here, we aimed to present the first checklist of vascular epiphytes in the Pedra Azul State Park and surroundings based on fieldwork and herbarium specimens. The checklist comprises 152 species, 65 genera, and 17 families, the main families being Orchidaceae, Bromeliaceae, and Polypodiaceae, with the main genera represented by Vriesea, Acianthera, and Peperomia. The holoepiphytes were the main category among the epiphytes, although an unusually high number of facultative epiphytes were recorded. Asplenium theciferum and Octomeria cucullata are recorded in Espírito Santo for the first time, and we confirmed the occurrence of Rhipsalis cereuscula in the state. Overall, the richness recorded in PA is amongst the highest of the Atlantic Forest cloud forests. Six species are threatened at the national level and 32 at the state level. These results support the importance of the protected area for conserving the flora; however, several species - including threatened - were only recorded in the surroundings, demonstrating that the buffer zone of the Pedra Azul State Park must be included in the management plans.
Keywords: Atlantic Forest; cloud forest; endangered species; floristic; inselberg; Pedra Azul State Park